SISTEM INFORMASI PENANGGULANGAN TUNA KARYA DAN ANAK JALANAN PADA DINAS SOSIAL KOTA PALEMBANGBERBASIS WEB - Muda, Seftia Putri ; Terttiaavini, Terttiaavini; Astuti, Lastri Widya (Universitas Bina Darma, 2018)
The street children and the jobless become the center for social welfare observers to find their way out. This is indeed the absence of data processing systems that can help data Management so there are still many unemployed children and the streets are hanging around. The purpose of the research to build information systems that record data street children and homeless. other than that the information system is supported by a web-based application that became a means of acceptance of public complaints. The application also provides information on statistics of street children and homeless. Keyword : The street children , Jobles, InformationSystem, Jobless,Website